2013
DOI: 10.1111/jphp.12114
|View full text |Cite
|
Sign up to set email alerts
|

In-vitro prediction of bioavailability following extravascular injection of poorly soluble drugs: an insight into clinical failure and the role of delivery systems

Abstract: The in-vitro model can be used as a cost-effective screening tool in injectable formulation development for safe and effective delivery of poorly soluble drugs. PDP can be circumvented with a well-designed formulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…This hypothesis was confirmed by comparing the AIC for models B and C. Our study design cannot elucidate the physiological determinants of a zero-order absorption profile of the tested aqueous solutions of lidocaine hydrochloride, but such atypical absorption behavior may be associated with the lymphatic uptake of precipitated drug molecules [27], or their dissolution by the rate-limiting turnover of interstitial fluid, resulting in pseudo zero-order absorption [30]. Further research is needed to confirm this hypothesized mechanism for lidocaine hydrochloride [33]. …”
Section: Discussionmentioning
confidence: 99%
“…This hypothesis was confirmed by comparing the AIC for models B and C. Our study design cannot elucidate the physiological determinants of a zero-order absorption profile of the tested aqueous solutions of lidocaine hydrochloride, but such atypical absorption behavior may be associated with the lymphatic uptake of precipitated drug molecules [27], or their dissolution by the rate-limiting turnover of interstitial fluid, resulting in pseudo zero-order absorption [30]. Further research is needed to confirm this hypothesized mechanism for lidocaine hydrochloride [33]. …”
Section: Discussionmentioning
confidence: 99%
“…The latter aspect is important in subcutaneous drug delivery, where macromolecular drugs injected into the adipose tissue need to pass through the extracellular matrix in order to be absorbed by the circulatory system via blood capillaries or lymphatic vessels [ 31 , 32 , 33 , 34 , 35 ]. Experiments have shown that positively charged therapeutic proteins are absorbed at a lower rate than net negatively charged proteins.…”
Section: Introductionmentioning
confidence: 99%
“…Lipid-and oil-based drug delivery systems are widely used for increasing the solubility and bioavailability of hydrophobic drugs [1][2][3][4][5]. Various types of nanostructured lipid carriers, liquid crystalline lipid nanoparticles (cubosomes, spongosomes, hexosomes, liposomes), microemulsions, nanoemulsions, nanogels, solid lipid nanoparticles, and hybrid lipid-polymer nanoparticles have been investigated with the aim of encapsulation and protection of poor soluble or instable therapeutic molecules [6][7][8][9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%